2020
DOI: 10.1186/s13018-020-01588-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms and expression levels of interleukin-6 and interleukin-10 in lumbar disc disease: a meta-analysis and immunohistochemical study

Abstract: Background: To investigate the association between interleukin-6 (IL-6) (rs1800795, rs1800796, rs1800797, rs13306435, rs2069849) and interleukin-10 (IL-10) (rs1800871, rs1800896) gene polymorphisms, expression levels, and lumbar disc disease (LDD). Methods: We conducted a literature research on PubMed, Embase, Web of Science, Cochrane Library, and China National Knowledge Infrastructure (CNKI) until February 28, 2019. We included all case-control studies about the association between IL-6 and IL-10 gene polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…The same study combined a meta-analysis, further indicating a significant association in the overall populations [17]. Other interleukins such as IL-4, IL-10 and IL-6, not discussed in this review, have also been associated with IVDD [8,12].…”
Section: Interleukin-1mentioning
confidence: 76%
See 1 more Smart Citation
“…The same study combined a meta-analysis, further indicating a significant association in the overall populations [17]. Other interleukins such as IL-4, IL-10 and IL-6, not discussed in this review, have also been associated with IVDD [8,12].…”
Section: Interleukin-1mentioning
confidence: 76%
“…Various association and linkage analyses studies have identified multiple genes attributed to the initiation and progression of IVD degeneration [8,9]. Amongst the pool of genes mentioned in the literature, we decided to focus on a total of 13 genes divided into a two-part series.…”
Section: Review Genetic Analysismentioning
confidence: 99%
“…Based on previous studies [20,21], 1000 Genomes Chinese Han Beijing population and dbSNP database (https:// www. ncbi.…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…These findings suggest that IL-6 played a crucial role in the occurrence of bone disease. The association of IL-6 rs2069837, and rs13306435 polymorphisms with the risk of rheumatoid arthritis and lumbar disc disease were assessed [20,21], but not studies on ONFH.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic association studies have shed light on the single nucleotide polymorphisms (SNPs) associated with IVDD susceptibility [ 5 ]. To date, numerous polymorphisms in genes encoding collagens [ 6 ], carbohydrate sulfotransferase (CHST) [ 7 ], interleukins [ 8 ], matrix metalloproteinases (MMP) [ 9 ], apoptosis-inducing ligand (TRAIL) [ 10 ] and growth differentiation factors (GDF) [ 11 ] have been investigated. These genes can be functionally incorporated into categories of intervertebral disc structure, structural support, cytokines, extracellular matrix-degrading enzymes, apoptotic factors, growth factors [ 5 ], each of which plays a different role in the development of disc degeneration.…”
Section: Introductionmentioning
confidence: 99%